1993
DOI: 10.1007/bf00058049
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of stromal cell stimulation in worsening the prognosis of a subset of patients with breast cancer

Abstract: This review examines the evidence that a subset of patients with breast cancer have tumors that are stimulated to grow by host cells in the tumor stroma. The search for such a minority group was prompted by the following observations. Adjuvant chemotherapy which is immunosuppressive improves disease-free interval and survival, whereas non-specific immunostimulation worsens the prognosis. Intrinsic immune reactivity is associated with a poor prognosis. A subset of tumors with a bad prognosis has anaplastic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…Breast tumours often contain large infiltrates of lymphocytes but the functional or prognostic significance of these cells is not clear despite decades of study (Stewart and Tsai, 1993;O'Sullivan and Lewis, 1994). Although it has been possible to isolate T cells that have cytolytic activity against the tumour in vitro, these cells seem to be unable to control tumour growth in vivo (Whiteside et al, 1986;Jerome et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Breast tumours often contain large infiltrates of lymphocytes but the functional or prognostic significance of these cells is not clear despite decades of study (Stewart and Tsai, 1993;O'Sullivan and Lewis, 1994). Although it has been possible to isolate T cells that have cytolytic activity against the tumour in vitro, these cells seem to be unable to control tumour growth in vivo (Whiteside et al, 1986;Jerome et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown T cells to be a favourable prognostic sign, whereas B cells are generally not predominant in various human cancers (Shimokawara et al, 1982). In contrast, some reports show evidence that tumours are stimulated into growth by host cells in the tumour stroma (Stewart and Tsai, 1993). In this context, in vitro studies demonstrated that tumour-infiltrating leucocytes display an immune inhibitory effect (Fulton, 1987;Vose and Bonnard, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant chemotherapy, in addition to its direct cytotoxic effect on cancer cells, might also attenuate surgery-stimulated tumour cell proliferation and angiogenic surge possibly occurring at distant dormant or indolent micrometastases (Retsky et al, 2004). Furthermore, adjuvant chemoradiotherapy may be effective by virtue of its cellular immune suppression and modification of specific host immunerelated mechanisms (Reizenstein et al, 1985;Stewart and Tsai, 1993).…”
Section: Discussionmentioning
confidence: 99%